Increasing Village Income Through FGD Participation with Socialization of the use of Digital Technology in Youth in Mlaras Village, Sumobito district, Jombang - Umami, Izzatul; Nurhayati, Wina; Auliya, Nanda Rahmah; Nurita, Rinta; Aziz, Muhammad; Janah, Miftakhul; Fazhira, Ira; Sa'diah, Aminatus; Nasution, Qustinanis Puja (Edumedia Solution, 2025)
Digital technology has become an important factor in increasing people's income, especially in rural areas that still face challenges in digital literacy. This research aims to optimize the use of digital technology to improve the economic welfare of the people of Mlaras Village, Sumobito District, Jombang Regency. The method is a participatory approach involving observation, socialization, training, and intensive mentoring. This program uses marketplaces, social media, and digital transaction systems to increase people's income.The study results showed a significant increase in digital literacy, which was 90%. People who previously relied on conventional methods are now more confident using digital technology to market products and conduct financial transactions. Some participants managed to increase revenue through online sales and the efficiency of digital transactions. With the increase in digital skills, the people of Mlaras Village are expected to continue to develop technology-based businesses and sustainably improve economic welfare. This program has a real positive impact and can be a model in developing a digital-based village economy.